Os processos de avaliação de sujeitos em privação de liberdade na 4ª Região Penitenciária do Rio Grande do Sul : dinâmica, contradições e mediações - Henrich, Giovana (2016)
The present study has as the central object the evaluations for granting benefits to subjects in deprivation of liberty, which purpose was configured to investigate how about the evaluations in the 4th Penitentiary Region of Rio Grande do Sul contributes to the rights effectiveness. The research that has an explanatory and qualitative nature, is based on the critical dialectical method and is conducted in the Prison System, bounded by the 4th Penitentiary Region of Rio Grande do Sul/Brazil. As a data source for the conduction of the study, an empirical research was made through interviews with social workers and psychologists from the prison system , in which the duty is aimed to the processes of evaluation, interviews with subjects in deprivation of liberty evaluated in 2014 and a documentary research through the evaluations made by the professionals about the same interviewed subjects in deprivation of liberty. The data analysis was done through the content analysis technique, based on Laurence Bardin’s theoretical framework. The obtained results reveal critical positioning by the professionals and by the subjects in deprivation of liberty, who were interviewed especially because such processes indicate historical characteristics relative to the prison system that guides the way the evaluations are made. Besides revealing the precarious working conditions to carry out such professional duty, the results also point to the moralizing and to the social adaptation perspective still intrinsic in the context, which is analyzed taking into consideration the contradictions of the system, as well as the reflections made by the professional categories involved in the issue. This way,it is observed that the evaluations for granting benefits to subjects in deprivation of liberty may contribute to the guarantee of rights as well as they may corroborate to the reproduction of processes that place the subjects as objects of a system socially excluding, reiterating practices of domination and discrimination once it also joins the professional practices carried out in such place. It is possible to verify through the research the professional critical understanding about that, however it is also possible to see the difficulty in translating the critique in the context of the evaluations, which shows that facing the reproduction of the violence in this object is still incipient, thus, demanding strengthening to consolidate practices less hierarchical - from the professionals to the penal system, and from the subjects in deprivation of liberty to the professionals and to the system – through new strategies to carry out the evaluation processes. In this sense emerges the thesis that the evaluations for granting benefits to individuals in deprivation of liberty imposed the questioning about the dynamics of the place that they occupy historically defining the professional assignments related to the theme. The professional assignments determined institutionally as well as the necessary conditions for the development of this work in the light of current legislation portray and are portrayed by the prison context setting up maintenance strategy and reproduction of the contradictions of institutional and social order that was historically constructed.